The Welfare Economics of International Adjustment - Willett, Thomas O.; Tower, Edward (Journal of Finance, 1971)
Thomas O. Willett, Edward Tower, The Welfare Economics of International Adjustment, The Journal of Finance, Vol. 26, No. 2, Papers and Proceedings of the Twenty-Ninth Annual Meeting of the American Finance Association Detroit, Michigan December 28-30, 1970 (May, 1971), pp. 287-302